An empirical analysis on technophobia/technophilia in consumer market segmentation - Adele Coppola; Fabio Verneau (Agricultural and Food Economics, 2014)
Many factors can affect the success of food product innovations. One such factor is the role played by consumer attitudes and psychological factors, especially the way consumers feel towards technology, their attitude towards risk, and the perceived relationship between nutrition and health. With a view to analysing these factors, this paper first identifies consumer groups using a technophobia/technophilia scale and then relates attitude to technology with purchasing behaviour regarding products which have a higher level of manipulation. A set of statements based on the psychometric scale proposed by Cox and Evans was administered to a sample of 355 individuals intercepted as they left supermarkets and hypermarkets. Principal component analysis and cluster analysis were applied to identify groups of homogeneous individuals with regard to the behaviour of the interviewees in relation to technology. Results show the presence of seven different groups, including a small group of convinced technophiles (13% of the sample). This group of early adopters can play an important role in promoting the use of innovative products, thereby contributing to a rapid increase in demand. Moreover, an important aspect was the result with respect to confidence attributed to the media in ensuring correct and unbiased information regarding new food technologies. Many of the respondents judged the media negatively in this respect. However, appropriate use of the media could be an important lever to counteract the attitude of caution or scepticism.
Keywords: 330; Psychometric scale; Consumption choices; Food innovation